(untitled) (Research, Society and Development, 2023)
Knowledge of the epidemiology of colorectal cancer helps in the planning and implementation of health measures to control this disease, which is so common in the Brazilian population. For this reason, the present study aimed to analyze the temporal trend of mortality rates due to colorectal cancer in Brazil and in its geographic regions between the years 2000 to 2020. The numbers of deaths due to malignant neoplasm of the colon (ICD-10: C18), the rectosigmoid junction (ICD-10: C19), the rectum (ICD-10: C20) and the anal canal (ICD-10: C21) available on the official portal of the Ministry of Health of Brazil for the period were analyzed, as well as the resident population data. The temporal and geographic pattern was analyzed using the age-standardized mortality rate (ASMR) and evaluated in a regression model using inflection points. The results showed that, regardless of gender, the ASMR grew by an average of 1.6% per year (AAPC: 1,6; CI95: 0,9-2,3) in Brazil. Growth was also observed in the Northeast (AAPC: 4,8; CI95: 4,1-5,5), North (AAPC: 4,4; CI95: 3,9-5,0), Midwest (AAPC: 1,8; IC95: 1,3-2,4) and Southeast (AAPC: 0,5; IC95: 0,2-0,8). The ASMR in the South region, regardless of gender, remained stable, but grew by an average of 0.7% per year (AAPC: 0,7; IC95 0,3-1,1) in the male population. Understanding these data can support the implementation of health measures in the country to meet the specific needs of each group and region.